Exploring the Strategies of Teachers to Integrate Tauhid in Teaching Science and History in Selangor, Malaysia - Hutapea, Riski Munandar; Husnaini, M; Victorynie, Irnie; Fuady, Ahmad Syauqi (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2021)
This study examines the teachers’ strategies to integrated Tawheed in teaching at Al-Amin Islamic Secondary School, Selangor. The purpose of this study is to explore the teachers’ perception of integrating Tawheed in teaching and to examine the strategies that have been practiced by teachers to integrated Tawheed in teaching. The teachers were purposively selected based on their experiences in teaching. This research employed a qualitative design by using the case study. The methodological triangulation was used for collecting the data, and the data was collected from oral interviews and classroom observations. A total of 5 teachers from Al-Amin Islamic Secondary School were selected to be interviewed and observed in the classroom. The data was analyzed using thematic analysis. The data from the interviews and observations were transcribed and the keywords were identified. Then, to start analysing the data, the researchers identified the theme and generated the sub-themes for further exploration. The findings showed that teachers’ perceptions in integrating tawheed in teaching were important to increase faith in Allah. Also, the researchers foundtwo strategies which were implemented by the teachers to integratetawheed in teaching namely teaching approaches and teaching methods. In teaching approaches, the teachers used both deductive and inductive approach. Besides, in teaching methods, the teachers applied story-telling, demonstrations and group discussion forintegrating tawheedto the students.